Incidence of grammar translation method in English Language learning in sixth and seventh elementary school students at Salle High School, during the school year 2006 - 2007 - Andrango Asmal, Pablo Mauricio (2007)
Our investigation is based on a practice teaching we did at "La Salle High School, in which we realized that students of sixth and seventh grades faced up some problems in EFL learning. The Grammar Translation Method has been used by "La Salle High School", for many years but the results obtained haven't been too effective since the students have problems in vocabulary knowledge, some basic grammar structures and especially in listening and speaking skills because they aren't able to use English Foreign Language communicatively. In order to know the consequences of the incidence of Grammar Translation Method in the students we developed surveys for teachers and students, a class observation and finally we applied a test to the students in which most of them had serious problems in Listening and Speaking, but in Writing and Reading they registered an acceptable level. Consequently, we recommended using not a specific method but some innovative strategies to apply in the classroom to teach children EFL by using a lot of visual aids such us: flash cards, worksheets, EFL games, songs sheets, outdoor activities, sock puppet dialogues, classroom posters, movies and many other classroom materials and strategies that help students to learn English without frighten and helpthem to get familiarized with EFL and get fun at the same time.